2021
DOI: 10.1007/s10508-021-01961-6
|View full text |Cite
|
Sign up to set email alerts
|

Neuroticism and Attention Toward Sexual and Non-Sexual Images During an Oddball Task: Evidence from Event-Related Potentials

Abstract: While previous research has argued that neuroticism is a vulnerability factor for the experience of sexual difficulties, the basic cognitive processes associated with the impact of such a personality trait on the processing of sexually explicit stimuli are less understood. The current study examined the influence of neuroticism on the attentional processes and its neurophysiological correlates during the perception of sexual and non-sexual images. Eventrelated potentials from 30 women and 28 men were recorded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
1
1
Order By: Relevance
“…As mentioned, the neuroelectric activity supporting this process was captured by the N2 component, but not by P1 or P2, which partially confirms our second hypothesis. Although a previous study [29] has identified a neuroticism effect on P1, in which women with high levels of neuroticism presented a significantly greater P1 latency for sexually explicit stimuli than for romantic ones, such effect was not identified in the current study. The fact that we only found an effect for N2 in our study could be attributed to fact that the N2 is thought to be sensitive to sexual images [26].…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…As mentioned, the neuroelectric activity supporting this process was captured by the N2 component, but not by P1 or P2, which partially confirms our second hypothesis. Although a previous study [29] has identified a neuroticism effect on P1, in which women with high levels of neuroticism presented a significantly greater P1 latency for sexually explicit stimuli than for romantic ones, such effect was not identified in the current study. The fact that we only found an effect for N2 in our study could be attributed to fact that the N2 is thought to be sensitive to sexual images [26].…”
Section: Discussioncontrasting
confidence: 88%
“…Several studies have empirically demonstrated the correlation between neuroelectric signals and cognitive aspects related to sexuality (see Ziogas et al [20], for a review), employing early attention ERP components. Recently, Carrito and colleagues [29] analysed the neuronal responses to sexual and non-sexual images between individuals presenting either high or low levels of neuroticism, and found that both neuroticism and the type of stimulus had an impact on P1 and P3 and, in the case of the former, also gender. With regards to the automatic attentional components, that study found a direct association between P1 latencies and neuroticism relatively to sexuallyexplicit stimuli when compared to romantic stimuli, but only in female participants.…”
Section: Neuroelectric Correlates Of Automatic Attentionmentioning
confidence: 99%